2018
DOI: 10.29309/tpmj/2014.21.01.1904
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Patterns

Abstract: Background: College students experience a number of sleep problems, which1impact academic performance, health, and mood . University students are exposed to pressuresdue to academic demands. Objectives: To determine the prevalence of sleep disorders amongcollege students and look into their sleep patterns and life style. Design: A cross-sectional study.Material & Method: Sample was comprised of 141 medical and non-medical students. Placeand Period of Study: The study was conducted at University of Lahore a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…In another literature study, they attributed this stress to the fact that medical students are overloaded with a tremendous amount of information as well as they have a limited amount of time to memorize all the information studied. The overload of information creates a feeling of disappointment because of the inability to handle all the information at once and succeed during the examination period [ 23 ]. Additionally, the majority (72.8%) of the participants in the current research had poor night sleep as it was reported by several studies among medical students [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another literature study, they attributed this stress to the fact that medical students are overloaded with a tremendous amount of information as well as they have a limited amount of time to memorize all the information studied. The overload of information creates a feeling of disappointment because of the inability to handle all the information at once and succeed during the examination period [ 23 ]. Additionally, the majority (72.8%) of the participants in the current research had poor night sleep as it was reported by several studies among medical students [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%